THE ROLE AND SIGNIFICANCE OF DIALECTS IN THE MODERN UZBEK LITERARY LANGUAGE: LINGUISTIC INTEGRATION AND DIFFERENTIATION - Bozorov Behruz Ilhom oʻgʻli (Ecomind Press, 2026)
This article explores the fundamental role of dialects (local varieties) in the formation, evolution, and enrichment of the modern Uzbek literary language. The Uzbek language possesses a unique dialectal structure, incorporating elements from three major Turkic groups: Karluk, Kipchak, and Oghuz. This research analyzes the reciprocal influence between dialectal lexis and literary norms, the stylistic functions of regionalisms in literature, and the challenges posed by globalization to dialectal diversity. The study concludes that dialects serve as the primary "genetic fund" for the literary language's continuous development.